Biodegradation of endocrine disruptors in urban wastewater using Pleurotus ostreatus bioreactor - Křesinová, Zdena; Linhartová, Lucie; Filipová, Alena; Ezechiáš, Martin; Mašín, Pavel; Cajthaml, Tomáš (New biotechnology, 2018)
The white rot fungus Pleurotus ostreatus HK 35, which is also an edible industrial mushroom commonly cultivated in farms, was tested in the degradation of typical representatives of endocrine disrupters (EDCs; bisphenol A, estrone, 17β-estradiol, estriol, 17α-ethinylestradiol, triclosan and 4-n-nonylphenol); its degradation efficiency under model laboratory conditions was greater than 90% within 12 days and better than that of another published strain P. ostreatus 3004. A spent mushroom substrate from a local farm was tested for its applicability in various batch and trickle-bed reactors in degrading EDCs in model fortified and real communal wastewater. The reactors were tested under various regimes including a pilot-scale trickle-bed reactor, which was finally tested at a wastewater treatment plant. The result revealed that the spent substrate is an efficient biodegradation agent, where the fungus was usually able to remove about 95% of EDCs together with suppression of the estrogenic activity of the sample. The results showed the fungus was able to operate in the presence of bacterial microflora in wastewater without any substantial negative effects on the degradation abilities. Finally, a pilot-scale trickle-bed reactor was installed in a wastewater treatment plant and successfully operated for 10days, where the bioreactor was able to remove more than 76% of EDCs present in the wastewater.
Keywords: Ligninolytic fungi; Biodegradation, Environmental; biodegradace; Waste Water; Water Pollutants, Chemical; Endocrine Disruptors; Bioreactor; bioreaktory; Pleurotus ostreatus; odpadní voda; Bioreactors; Wastewater; Wastewater treatment; endokrinní disruptory; Pleurotus; chemické látky znečišťující vodu; Endocrine disruptors